Meningkatkan Keterampilan Berbicara melalui Metode Sosiodrama pada Siswa Kelas IV SDN 5 Kesu’ - Eky Setiawan Salo (Jurnal Keguruan dan Ilmu Pendidikan, 2021)
This research is a classroom action research that aims to improve speaking skills using the sociodrama method in Indonesian subjects for fourth grade students at SDN 5 Kesu'. This classroom action research was conducted in two cycles and in each cycle consisted of four steps of activities, namely planning, implementation, observation, and reflection. The results showed that using the sociodrama method in Indonesian language learning was able to increase students' self-confidence, intonation, diction, fluency and expression in students' speaking skills. The results of the analysis state that the results of the fourth grade students of SDN 5 Kesu' speaking skills have increased, seen from the average cycle 1 of 66% and cycle II of 78%. Theauthor concludes that the sociodrama method can be used in learning Indonesian because it can increase self-confidence, intonation, diction, fluency of speech and expression in speaking skills.